Recruiting Older Adults With Functional Difficulties Into a Community-Based Research Study: Approaches and Costs - Nkimbeng, Manka (J Appl Gerontol, 2018)
The CAPABLE (Community Aging in Place, Advancing Better Living for Elders) trial in Baltimore City tested whether an interdisciplinary team of occupational therapists, nurses, and handymen reduces disability and health expenditures in community-dwelling older adults with functional difficulties. This study describes methods and associated costs of recruiting 300 low-income, cognitively intact, older adults with functional difficulties into this study. Sources of participant enrollment included direct mailings (35%), government program referrals (19%), community-based organizations (16%), ambassador referrals (15%), and media (4%). Fifty six (30%) of 187 older adults referred through government organizations were enrolled, while 49 (7.6%) of 648 referred from community-based organizations were enrolled. Total recruitment costs were US$81,453.12. Costs per participant for mailings, media, ambassadors, and community-based organizations were respectively US$745.10, US$256.82, US$22.28, and US$1.00. Direct mailings yielded the most participants but was the most costly method per participant. Ambassadors were least expensive and may offer a low-cost addition to community outreach for recruitment of older adults into research.